Principles Governing the Use of International Rivers for Non-Navigational Purposes - Fathi Abdel-Jalil , Wed; Jabbar Kreidi Al-Qadi , Prof. Dr. Ali (Basra studies journal, 2022)
International law was concerned with the issue of international rivers and their use for non-navigational purposes. And, the study of water received a special priority at the present time. According to population growth and economic development, the supply and demand for water in the Arab world increased. The political pressures are viewed by the unfair exploitation of water by the countries of the source of the rivers. Nowadays, these countries build dams and large water projects that imprison water and store it in large quantities. This, greatly and seriously affects the security of those countries and makes it brittle to the political challenges. There are several principles and rules regulating the operations of using the waters of shared rivers at the international level. The agreement on the use of estuaries for non-navigational purposes came in 1997 AD to stipulate in its articles and refer to these principles, which must be observed and respected by the basin countries.